In vitro Growth of Cattleya sp Orchid from Leaf Explants with Growth Regulators - Harahap, Fauziyah; Hariyadi, Itra; Silitonga, Melva; Suryani, Cicik; Edi, Syahmi; Ningsih, Ayu Putri (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Using leaf explants, this research aimed at identifying the type of growth response that can be created and the optimal mix of media for the growth of Cattleya sp orchid. This was an experimental investigation employing the RAL method (completely randomized design) with a combination of 2.4-D (0;1; 2; 3 ppm) and Kinetin  (0;0.3;0.6 ppm) repeated three times. According to the results of this study, the growth regulators 2.4-D and kinetin  were unable to promote the development of all explants. Explants transferred to media containing polyvinylpyrrolidone (PVP) to prevent browning after 12 weeks of observation. Then the results of the study also found the emergence of shoots in the treatment P0 (control), P2 (2,4-D 0 + Kinetin  0.6 ppm), P8 (2,4-D 2 + Kinetin  0.6) and P11 (2.4- D 3 + K 0.6 ppm) in the 3rd week of observation, the appearance of callus at P5 (2.4-D 1 + Kinetin  0.6 ppm) in the 4th week of observation